Genetic diversity for characteristics of ‘Ubá’ mango tree fruit - Oliveira, Girlaine Pereira; da Silva, Danielle Fabíola Pereira; Siqueira, Dalmo Lopes de; Salomão, Luiz Carlos Chamhum; Pires Matias, Rosana Gonçalves (Científica, 2018)
The objective of this study was to evaluate the genetic diversity for physical and chemical characteristics of fruits of 47 ‘Ubá’ mango accessions in the Zona da Mata Mineira. The fruits physiologically mature of the 47 accessions were coming from the experimental orchard of Fazenda Sementeira, located in the Municipality of Visconde do Rio Branco-MG, an orchard of the Federal University of Viçosa, MG. The fruits were harvested and analyzed for the following characteristics: fruit mass (g); flesh firmness; peel and pulp color; percentage of seeds, peel and pulp; titratable acidity (TA); soluble solids (SS); vitamin C; and carotenoids. A completely randomized design was used, with 47 accessions, four replications (plants per access), and twenty fruits per plot (five fruits per plant). Dissimilarity measures were obtained, and clustering techniques were applied for the subsamples. The most similar accessions were 34 and 48, and the most distant were 11 and 55; carotenoid content was the characteristic that most contributed to the divergence between accessions. The cluster analysis showed the formation of two groups by the Tocher and UPGMA methods, which demonstrates the existence of genetic variability in ‘Ubá’ mango trees in the Zona da Mata of Minas Gerais. In view of this, the accessions discussed here have potential for use in breeding programs, aiming at obtaining good materials for the industry.